НАВЧАННЯ ОСНОВ ПЕДАГОГІЧНОГО СПІЛКУВАННЯ В ВИЩІЙ ШКОЛІ СІЛА (Педагогіка вищої та середньої школи, 2022)
The article deals with the problem of training in basics of pedagogical communication at USA higher colleges as a factor of professional development of the future specialist by means of training in intensive communication groups, creating laboratories of pedagogical guidance and pedagogical tutorship.